Combining frost tolerance, high grain yield and good pasta quality in durum wheat. Issue 4 (28th April 2013) - Longin, Carl Friedrich Horst; Sieber, Alisa‐Naomi; Reif, Jochen C.
Abstract: Growing in Central Europe winter instead of spring durum wheat would substantially increase yield potential but is currently hampered by the lack of knowledge of frost tolerance present in elite material. The objectives of our survey were to (i) study the genetic variability and heritability of frost tolerance and its association with other important agronomic and quality traits in durum wheat, (ii) examine the potential to combine frost tolerance with high quality and high grain yield and (iii) investigate the consequences of the heritabilities and associations among traits on the optimum design of a multistage selection programme for winter durum wheat. We investigated 101 elite winter durum wheat lines and four commercial checks in field trials at four locations. Four agronomic as well as nine quality traits were recorded. In addition, frost tolerance was evaluated using a semi‐controlled test resulting in high‐quality phenotypic data. Genotypic variances (σ²G ) were significantly larger than zero for all traits, and heritabilities were moderate to high. Several elite durum wheat lines exhibited a frost tolerance comparable to that of two frost‐tolerant Triticum aestivum varieties. Frost tolerance was not negatively associated with other important agronomic and quality traits. The high quality of the phenotypic data for frost tolerance evaluated in a semi‐controlled test suggests that this is a cost‐efficient approach to consider frost tolerance at early stages of a multistage durum wheat breeding programme.